Cardiac calcified amorphous tumor as a potential cause of cerebral infarction: A clinical case report - Hyunjin Kim, MD; Shotaro Kanao, MD, PhD; Satoshi Noma, MD, PhD; Sumika Yasumura, MD; Shinji Sumiyoshi, MD, PhD; Manabu Morishima, MD, PhD; Takeshi Kubo, MD, PhD (Radiology Case Reports)
We report the case of a 62-year-old male on long-term hemodialysis who was admitted to our hospital due to acute cerebral infarction associated with a cardiac calcified amorphous tumor (CAT). The patient presented with recurrent episodes of syncope and retrograde amnesia. Brain MRI identified multiple acute cerebral infarctions, while transthoracic echocardiography (TTE) revealed a 2.5 cm echogenic mobile mass attached to the ventricular side of the posterior mitral leaflet. The patient underwent surgical resection of the mass. Pathological examination confirmed the diagnosis of a CAT. A chest computed tomography (CT), performed incidentally for pneumonia 6 months prior, revealed extensive calcifications in the mass. Postinfarction imaging showed a reduction in calcifications within the mass, suggesting a potential link between the infarction and changes in the cardiac lesion.